Orthoplastic Limb Salvage of a Gustilo-Anderson Grade IIIB Open Trans-Articular Knee Fracture: A Case Report on Staged Reconstruction with a Rotational Fasciocutaneous Flap - Satriya Teguh Imam; Amru Sungkar; Rhyan Dharma (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: High-energy, open trans-articular knee fractures with extensive soft-tissue loss represent a formidable challenge, carrying a high risk of deep infection, nonunion, and amputation. Successful limb salvage necessitates a collaborative orthoplastic approach, combining aggressive surgical debridement and skeletal stabilization with timely, vascularized soft-tissue coverage. Case presentation: A 16-year-old male was admitted after a severe traffic accident, sustaining a Gustilo-Anderson Grade IIIB open fracture of the right knee. The injury comprised a comminuted distal femur fracture, a comminuted tibial plateau fracture (Schatzker VI), a comminuted patellar fracture, and a proximal fibula fracture. A 12x15 cm soft-tissue defect with a depth of 6 cm exposed the joint capsule and all fracture sites. The patient underwent a staged management protocol. The initial surgery involved extensive debridement of non-viable tissue and stabilization with a spanning multi-planar external fixator, followed by a second-look debridement. Definitive coverage was achieved on day five with a large, medially-based rotational fasciocutaneous flap and a split-thickness skin graft over the donor site. At the 1-year follow-up, all fractures had united, and the soft-tissue envelope was stable and sensate. The patient achieved a functional knee range of motion of 0-100 degrees and could ambulate without aids. The Lysholm knee score was 85, and the Knee Society Score (KSS) was 88. Conclusion: This case report demonstrates that a meticulously planned, staged orthoplastic strategy can achieve successful limb salvage even in devastating open knee injuries. A large, local rotational fasciocutaneous flap can serve as a reliable and less complex alternative to free tissue transfer for covering massive defects in this region, particularly in young patients with favorable tissue characteristics.